Gestational exposure to fatal police violence and pregnancy loss in US core based statistical areas, 2013–2015. (June 2021) - Jahn, Jaquelyn L.; Krieger, Nancy; Agénor, Madina; Leung, Michael; Davis, Brigette A.; Weisskopf, Marc G.; Chen, Jarvis T.
Abstract: Background: Fatal police violence in the United States disproportionately affects Black, Native American, and Hispanic people, and for these groups it is a racially oppressive population-level stressor that we hypothesize increases the risk of pregnancy loss. Focusing on core based statical areas (CBSAs) surrounding small and large urban centers, we accordingly tested whether gestational exposure to fatal police violence decreased the number of live births, which is reflective of a rise in lost pregnancies. Methods: Our observational study linked microdata for all births ( N  = 7, 709, 300) in 520 CBSAs with at least one incident of fatal police violence in 2013–2015 to Fatal Encounters, a database that prospectively identified 2594 police-related fatalities using online media reports and public records. We estimated the association between month-to-month fatal police violence and conceptions resulting in live births using distributed lag quasi-Poisson models with CBSA-level fixed effects, adjusted for seasonality and stratified by maternal race/ethnicity. Findings: For each additional police-related fatality that occurred in the first through sixth months of gestation, we observed a 0.14% decrease (95% confidence interval: 0.05%, 0.23%) in the total number of live births within CBSAs, and a 0.29% decrease in births to Black women (95% CI: 0.11%, 0.48%). The association was null for births to White women. Interpretation: Our findings suggest fatal police violence may have population-level consequences for pregnancy loss and adds to the evidence regarding the importance of preventing these fatalities. Funding: This study was supported in part by NIH grant P30ES00002 to MGW.